Pelatihan Penulisan Artikel Berbasis Action Research pada Guru Biologi MA/Mts di Tidore Kepulauan - Astuti Muh Amin; Juniartin Juniartin; Muhammad Matdoan (To Maega : Jurnal Pengabdian Masyarakat, 2023)
The ability to carry out classroom action research is one of the abilities that must be possessed by professional teachers. The general objective of Community Service (PkM) is to provide understanding and training related to writing action research-based scientific articles for MA/Mts biology teachers in Tidore, Islands, North Maluku. Participants in the training activities were biology teachers at the MA/MTs level in the Tidore Islands, North Maluku, totaling 30 people. The methods used are the lecture method, question and answer, presentation, and drill. The results of PkM activities show (1) there is an increase in understanding and motivation of activity participants in writing Action Research-based scientific articles with an average response value of 98.33%; (2) activity participants have been able to identify problems in the learning process in class for the basis of conducting research and writing scientific articles based on Action Research; (3) OJS Al-Nafis Journal, Tadris Biology IAIN Ternate have been socialized to PkM participants. Even so, PkM activities still need to be continued in the form of continuous intensive assistance.Â